Performance analysis of a wind farm on transmission network using DIgSILENT power factory. (12th May 2021) - Ucheniya, Ravi; Saraswat, Amit; Siddiqui, Shahbaz Ahmed; Goyal, Sunil Kumar; Kanwar, Neeraj
The non-linearity and complexity of the power network are increased with an ever-increasing inclusion of renewable energy sources to its existing grid. It necessitates more computational efforts from the system operator for its reliable and safe operation. In parallel, new ideas and emerging technologies have been evolved worldwide to improve system reliability and stability. However, the complexity of power networks has increased so much that direct implementation of any new technology on the system can be very complex and sometimes quite risky. Therefore, appropriate simulation software is needed to reduce the above restriction. In this paper, DIgSILENT power factory simulation software has been used to simulate an 80 MW wind farm, using sixteen wind turbines (5 MW each). The performance analysis of the developed wind farm has been carried out on the IEEE 30 bus standard test system. Comparative analysis of the results obtained during the validation of the network as well as optimisation of total cost and loss has been carried out.